RANDOMIZED TRIAL FOR COMPARISON OF BUPRENORPHINE AND FENTANYL FOR AWAKE FIBEROPTIC INTUBATION - GOYAL, GAURAV; kiran yadav; Kalpana Verma; GUPTA, NAMITA; Sudhir sachdev (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Awake fiberoptic intubation (AFOI) is a step-forward technique for successful intubation of patients with difficult airways. The popularity of its usage is increasing day by day in handling difficult airways. Our study aims to compare the efficacy and efficiency of Buprenorphine and Fentanyl as sedative agents for AFOI. The primary and secondary outcome measure was to assess hemodynamic response and on intubating condition of the patient after AFOI. Methods: This randomized, prospective study was conducted in tertiary Center hospital. Total of 100 patient were enrolled for study and divided into two groups, Group A patients received intravenous Buprenorphine injection (2.5 (microgram/kilogram [μg/kg] over 10 min) and Group B Fentanyl injection (2 μg/kg over10 min) was injected prior to AFOI. The degree of sedation was assessed using the Observer’s assessment of alertness/sedation score (OAA/S), and the score of coughing during awake bronchoscopy was used to assess intubation status. Tolerability of intubation was assessed using a 5-point intubation score and a 3-point post-intubation assessment score immediately after the placement of the endotracheal tube into the trachea. Results: Group A had more favorable OAA score than Group B, whereas other intubation conditions cough score, limb movement, 5-point intubation score, 3-point post intubation score was more favourable in Group B than in Group A. Conclusion: Intravenous Fentanyl is better than Buprenorphine agent in terms of intubation score for AFOI. Both groups are comparable in terms of hemodynamic changes and stability.